(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article is devoted to topical problems of preparing future teachers for the use of digital technologies at a high level. There is a need to review existing curricula and subjects to develop future teachers’ digital skills in the educational process. A special place in the training of future teachers is occupied by organizations based on the digitalization of methods of teaching school subjects.